2020
DOI: 10.1111/hsc.13109
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the capacity of community‐based organisations to absorb health system patient referrals for unmet social needs

Abstract: This study examines the perspectives, resources, role and services provided by community‐based organisations (CBOs) in response to the integration of health and social services to address individual unmet social needs, as well as the impact on organisational carrying capacity related to the ability to receive referrals from health system partners. Mixed methods combining qualitative interviews with 24 organisations and Social Network Analysis with 75 organisations were completed in 2018 in two communities (Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…32 Another study of 2 regional attempts to integrate health and social services found that community organizations were in wellconnected cross-sector networks (number of connections), but were not fully prepared for the resultant increases in referrals from the health system due to insufficient funding and lack of referral coordination. 87 Network characteristics also played a role in outcomes. For organizations involved in sharing administrative and client information, stronger linkages correlated with higher perception of network administration and service delivery effectiveness.…”
Section: Thematic Categoriesmentioning
confidence: 99%
“…32 Another study of 2 regional attempts to integrate health and social services found that community organizations were in wellconnected cross-sector networks (number of connections), but were not fully prepared for the resultant increases in referrals from the health system due to insufficient funding and lack of referral coordination. 87 Network characteristics also played a role in outcomes. For organizations involved in sharing administrative and client information, stronger linkages correlated with higher perception of network administration and service delivery effectiveness.…”
Section: Thematic Categoriesmentioning
confidence: 99%
“…Community-based organizations (CBOs) may be well-positioned to support primary care clinics in addressing the social factors of depression given their focus on social needs and often high-standing in lower-resourced communities [35,36]. However, previous studies have suggested CBO and clinical partners are often misaligned in their understandings of capacity and demand, leaving CBOs to absorb high volumes of referrals they may not have capacity to address [37]. Thus, we argue crossorganizational partnerships that integrate social care services and establish lines of communication beyond traditional referral models may help to alleviate these de cits and improve care.…”
Section: Discussionmentioning
confidence: 99%
“…To do this, community-based and person-focused paradigms of care must be strengthened [ 63 ] and community stakeholders must be considered as co-producers of care [ 64 ] and, ultimately, as co-builders of social policies [ 21 ] for people with complex needs. Decision makers must consider adequate funding [ 60 ] dedicated to community stakeholders participation in individualized service plans [ 65 , 66 ] and their engagement in CMPs. In the same way, the programs need to be supported and pursued in a perspective of ongoing improvement.…”
Section: Discussionmentioning
confidence: 99%